Analysis of Public Service Digitalization in the Creation of Population Identities at Padurenan Village, Bekasi City - Bambang Diana; Elvira Gina Hamada; Yusup Lintang Cahyo Andrian Putro (Catalist Indo Publisher, 2025)
Background The digitalization of public services has become one of the most important aspects of modernizing government administration, with the main goal of increasing the efficiency, transparency, and accessibility of services to the public. Methods This research uses a descriptive qualitative method with a case study approach, involving interviews with relevant parties at the village level, such as government officials and local residents. Results The research results show that digitalization provides convenience in terms of time efficiency, queue reduction, and ease of access to information through an integrated system. However, this study also identifies a number of constraints that are still faced, such as limited access to technology in some segments of society, low levels of digital literacy, and a lack of training and understanding of how to use existing digital systems. Conclusions The digitalization of public services in the creation of population identities in Padurenan Village has had a positive impact on improving the efficiency of public services. The implementation of the Digital Population Identity (IKD) system allows citizens to verify their identity quickly and easily without needing to carry a physical ID card. Therefore, the successful implementation of digitalization depends not only on technological development but also on strengthening digital education for the public and improving supporting infrastructure.